Aplikasi metode association rule pada promosi produk - Khirdany, Elvin Nury; Islamy, Sulaiha Nor; Aini, Laily Nur; Maghfiroh, Lailatul (Journal of Management and Digital Business, 2022)
Product promotion is important by utilizing customer opinion to help choose products. A cafe is a place that many people visit, so it requires product promotion. Knowing the types of products that are often purchased can be used to determine what products are suitable to be promoted to customers. Therefore, it requires a method used for product promotion using association rules using support and confidence parameters. The results obtained are: If customer support for buying onion rings is 18%, then the confidence in latte americano is 60%. If customer support for buying onion rings is 25%, then orange juice confidence is 80%. If customer support for buying an iced latte is 13%, then confidence in onion rings is 66%. If customer support for buying onion rings and latte americano is 13%, then the confidence in orange juice is 67%. If customer support for buying onion rings and latte americano is 13%, then confidence in an iced latte is 67%.